2014
DOI: 10.1152/ajpheart.00244.2014
|View full text |Cite
|
Sign up to set email alerts
|

Obesity increases inflammation and impairs lymphatic function in a mouse model of lymphedema

Abstract: Although obesity is a major clinical risk factor for lymphedema, the mechanisms that regulate this effect remain unknown. Recent reports have demonstrated that obesity is associated with acquired lymphatic dysfunction. The purpose of this study was to determine how obesity-induced lymphatic dysfunction modulates the pathological effects of lymphatic injury in a mouse model. We used a diet-induced model of obesity in adult male C57BL/6J mice in which experimental animals were fed a high-fat diet and control ani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
86
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 121 publications
(98 citation statements)
references
References 31 publications
7
86
0
5
Order By: Relevance
“…This hypothesis is also supported by previous studies demonstrating that CD4 + cells are key regulators of smooth muscle cell proliferation and atherosclerosis (46)(47)(48), as well as studies demonstrating that ECM composition is a key regulator of interstitial fluid transport (49). Progressive lymphatic and ECM fibrosis also provides a rationale for known risk factors of lymphedema, such as radiation and obesity, as these factors independently increase fibrosis (50)(51)(52). Indeed, previous studies have shown that radiation-induced fibrosis markedly decreases interstitial fluid transport and that inhibition of fibrosis effectively preserves lymphatic function independent of LEC survival in this setting (53).…”
Section: Discussionsupporting
confidence: 68%
“…This hypothesis is also supported by previous studies demonstrating that CD4 + cells are key regulators of smooth muscle cell proliferation and atherosclerosis (46)(47)(48), as well as studies demonstrating that ECM composition is a key regulator of interstitial fluid transport (49). Progressive lymphatic and ECM fibrosis also provides a rationale for known risk factors of lymphedema, such as radiation and obesity, as these factors independently increase fibrosis (50)(51)(52). Indeed, previous studies have shown that radiation-induced fibrosis markedly decreases interstitial fluid transport and that inhibition of fibrosis effectively preserves lymphatic function independent of LEC survival in this setting (53).…”
Section: Discussionsupporting
confidence: 68%
“…To address this question, we compared lymphatic function in obesity-prone and obesityresistant mice after prolonged exposure to HFD. Our results are consistent with previous reports demonstrating that C57BL/6J mice become morbidly obese on HFD feeds, 8,9 while BALB/cJ and MSTN ln mice do not 21,22 even though serum FFA levels were significantly increased in all HFD-fed mice. 13,35 This approach is clinically relevant as the incidence and severity of obesity in patients is also highly variable and modulated by genetic factors.…”
Section: Discussionsupporting
confidence: 93%
“…[3][4][5][6][7][8][9][10] However, it remains unclear whether the observed effects on lymphatic function were secondary to weight gain, prolonged exposure to HFD or toxic metabolic by-products of adipose tissue. To address this question, we compared lymphatic function in obesity-prone and obesityresistant mice after prolonged exposure to HFD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies suggest that potential risk factors for developing lymphedema include radiation therapy, infection, axillary dissection, type of surgery, the number of lymph nodes removed and involved, and obesity. Even though it is not known whether these factors affect the severity of lymphedema 6 , obesity can be associated with increased chronic inflammation, fibrosis and adipose deposition 9 , therefore obese or overweight women are at higher risk for lymphedema. The purpose of this study was to investigate the influence of BMI of women who underwent survey with axillary dissection for breast cancer on the occurrence of lymphedema and other complications such as scar tissue adhesion, pain, and heaviness in the upper limb within two years after surgery.…”
Section: Introductionmentioning
confidence: 99%